2017
DOI: 10.7554/elife.23588
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel determinants of endothelial lineage using chimeric heterokaryons

Abstract: We wish to identify determinants of endothelial lineage. Murine embryonic stem cells (mESC) were fused with human endothelial cells in stable, non-dividing, heterokaryons. Using RNA-seq, it is possible to discriminate between human and mouse transcripts in these chimeric heterokaryons. We observed a temporal pattern of gene expression in the ESCs of the heterokaryons that recapitulated ontogeny, with early mesodermal factors being expressed before mature endothelial genes. A set of transcriptional factors not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…To examine the Tbx20 gene expression in endothelial differentiation, two model systems were used, one is the mESC differentiation to ECs and the other one is heterokaryon induced differentiation of pluripotent stem cells into endothelial lineage. During the mESC differentiation into endothelial lineage 18 , Tbx20 gene expression was upregulated by 16-fold at day 8 of differentiation compared with mESCs (Fig. S1a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To examine the Tbx20 gene expression in endothelial differentiation, two model systems were used, one is the mESC differentiation to ECs and the other one is heterokaryon induced differentiation of pluripotent stem cells into endothelial lineage. During the mESC differentiation into endothelial lineage 18 , Tbx20 gene expression was upregulated by 16-fold at day 8 of differentiation compared with mESCs (Fig. S1a).…”
Section: Resultsmentioning
confidence: 99%
“…S1a). In a heterokaryon model 18 , fusing mESC with HUVECs induced differentiation of pluripotent stem cells toward endothelial lineage. We found that Tbx20 gene expression was upregulated and peaked at 4-fold at 6 hours after heterokaryon formation compared with co-culture control (CT, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an excellent approach to obtaining a global view of the transcriptional activity of a cell. An analysis of RNA-seq data can reveal novel transcripts that are determinants of phenotype and function (2). However, the amount of data obtained from RNA-seq can be overwhelming.…”
Section: Pericytes and Vascular Homeostasismentioning
confidence: 99%